An Analysis of Idiomatic Expression Presented in the New Songs of the Album Positions by Ariana Grande - Roger, Jocelynne Victoria; Ariyaningsih, Ni Nyoman Deni (Vivid: Journal of Language and Literature, 2023)
The idiomatic expressions is a common phenomenon in language use as a communication tool between humans. The use of idiomatic expressions can be presented in the dialogue and expressed in a literary work, such as in a song. It led the researcher to study further 1) the types of idiomatic expressions and 2) the meanings presented in the idiomatic expressions of 6 songs in "Positions" album by Ariana Grande. The researcher used qualitative research techniques combined with observation methods.Meanwhile, to analyze the data, the researcher used McCarthy & O'Dell's(2010) theory to specify the type of expression and Leech's (1981) theory to describe the meaning presented in the idiomatic expressions. The result discovered 18 data that belong to idiom expressions, with details: fixed statements (14), trinomials (3), and prepositional phrases (1). Each idiom expression has its specific meaning, which aims to enable the audience to understand the true meaning. According to Leech (1981), all the meaning presented in the idiom expressions belongs to thematic meaning.